A feasibility trial of pulmonary rehabilitation for patients with COPD in a low resource setting: Jaffna, Sri Lanka - Mathanki Sooriyakanthan; Mark W. Orme; Kanagasabai Sivapalan; Gowry Selvaratnam; Sally J. Singh; Savithri Wimalasekera (BMC Pulmonary Medicine, 2022)
Abstract Background Pulmonary rehabilitation is recommended for most patients with chronic obstructive pulmonary disease (COPD). Accordingly, the aim of this study was to explore the feasibility of devising a pulmonary rehabilitation program for patients with COPD in a low resource setting (Jaffna, Sri Lanka) and to observe its effects. Methods Non-randomized controlled feasibility trial of ambulatory patients with COPD attending the pulmonary outpatient clinic of the Jaffna Teaching Hospital, Northern Province, Sri Lanka. Age-matched patients were allocated alternatively to an intervention group or to a control group. Twice weekly, for six weeks, patients in the intervention group attended pulmonary rehabilitation sessions consisting of supervised stretching, aerobic and strengthening exercises, and patient-education. Before and at the conclusion of the study, all patients performed incremental shuttle walking test (ISWT), 6-min walk test (6MWT) and completed the Medical Research Council (MRC) dyspnea scale, COPD assessment test (CAT), chronic COPD questionnaire (CCQ), and hospital anxiety depression scale (HADS). Results 204 patients with COPD (94% males) were identified at screening; 136 (66.7%) were eligible for pulmonary rehabilitation and 96 patients (47%) consented to participate. Of these, 54 patients (53 males) eventually participated in the study (42 patients were discouraged to participate by family members or friends); 40 patients (20 in the rehabilitation group and 20 patients in the control group) completed the study. Baseline characteristics of the intervention group and the control group were similar. 95% of patients in the intervention group adhered to regular home training exercises (self-reported diary). At post assessment, only the intervention group experienced clinically-meaningful improvements in symptoms and exercise capacity. Conclusion A simple and clinically beneficial pulmonary rehabilitation program for patients with COPD can be effectively implemented in a low resource setting. However, there is a need for educating patients and the local community on the benefits of pulmonary rehabilitation to enhance uptake. Retrospective Trial Registration date and number: 16/04/2021, ISRCTN10069208.